Russian roulette from the Euromaidan protest to the Ukraine invasion: Is it different this time? - Mohamad, Azhar (2022)
We scrutinise the impact of two periods of Russo-Ukraine strife: (a) the Russo-Ukraine war that started in February 2022; and (b) the Euromaidan protest of November 2013, on the financial markets. We observe severe ramifications in terms of abnormal returns, price discovery and time-varying herding between certain group of assets. Whereas the US dollar and the yen consistently serve as safe haven assets (proxied by negative or low unconditional correlations) to opposing countries' stock indexes and currencies in both periods, we generally document heterogeneity in the financial assets' degree of response to them.